2020
DOI: 10.1007/s40436-020-00328-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of flow and debris ejection in blasting erosion arc machining in end milling mode

Abstract: Blasting erosion arc machining (BEAM) is a typical arc discharge machining technology that was developed around 2012 to improve the machinability of difficult-to-cut materials. End milling BEAM has been successfully developed and preliminarily applied in industry. However, owing to the high complexity of the flow field and the difficulty of observing debris in the discharge gap, studies of the flow and debris in end milling BEAM are limited. In this study, fluid dynamics simulations and particle tracking are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Therefore, establishing a high-precision prediction model of noise in the high-speed milling of WPCs and reducing the noise in high-speed machining by selecting appropriate cutting parameters are of great significance. Sampath et al [ 7 , 8 ] used a finite element model to predict the sound pressure generated during the high-speed end milling of aluminum alloy and found that cutting parameters and tool geometry parameters have important effects on noise. Karakurt et al [ 9 ] used multiple regression analyses to establish a noise model and found that cutting speed has the greatest influence on noise level among the cutting parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, establishing a high-precision prediction model of noise in the high-speed milling of WPCs and reducing the noise in high-speed machining by selecting appropriate cutting parameters are of great significance. Sampath et al [ 7 , 8 ] used a finite element model to predict the sound pressure generated during the high-speed end milling of aluminum alloy and found that cutting parameters and tool geometry parameters have important effects on noise. Karakurt et al [ 9 ] used multiple regression analyses to establish a noise model and found that cutting speed has the greatest influence on noise level among the cutting parameters.…”
Section: Introductionmentioning
confidence: 99%